Етномистецька компетентність майбутніх викладачів музичного мистецтва: регіональний аспект - Смирнова Тетяна; Smyrnova Tetiana; Телеп Оксана; Telep Oksana (Видавництво «Код», 2025)
Резюме. У статті розглянуто сутність, принципи етно-мистецької компетентності майбутніх викладачів музичного мистецтва, окреслено зміст етно-мистецької освіти студентів (поняття, способи народно-мистецької діяльності, досвід народної творчості, система етно-цінностей) на прикладі навчального курсу для бакалаврів «Музичний фольклор Закарпаття».

Abstract. The article examines the essence and principles of ethno-artistic competence of future teachers of music, the content of ethno-artistic education for students is outlined (concept, methods of folk art activity, experience of folk art, system of ethno vaiues) on the example of the educational course for «Musical Folklore of Transcarpathia». The term ethno-artistic competence is defined as the professional importance of an individual who integrates a complex of knowledge as a holistic system of information about folk art( facts, ideas, theories, positions), methods of artistic activity, experience of its implementation, inherent in a certain ethnic group, experience of creative activity in a certain field of folk art ( original interpretations, local folk performance styles, specific genres, variations and combinations), experience of value-oriented activities of representatives of the national ethnic group (a system of folk ideals, norms, rules, traditions, ideas, values, inherent in a certain direction of folk art). The content of the principles of ethno-artistic competence is substantiated. The principle of ethnic identity emphasizes the value of preserving the inner peace and soui of the Ukrainien people, the principle of ethnicity, his ethnic interests, actions, motives, thoughts. The principle of ethnic consciousness affirms the understanding of the significance of the integrity of the Ukrainian ethnic group. The principle of ethnicity emphasizes the role of students who transmit the values of folk art from the past to the future. The principle of artistic ethnic integration and consolidation focuses on uniting divided ethnic communities and ethnic processes into a single whole. The principle of artistic and cultural education means combining ethno artistic concepts, terms, methods of activity, and values of folk art in the content of students artistic education.
Ethno-artistic competentence of future teachers of musical art regional aspect
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: музичне мистецтво; майбутні викладачі музичного мистецтва; етнос; етно-культура; компетентність; заклади вищої освіти; Закарпаття; мистецька освіта